Service Quality Perspectives and Satisfaction in Health Care Systems-A study of select hospitals in Hyderabad - Deshpande, Priya (Indian Journal of Marketing, 2006)
Liberalization, Privatization and Globalization (LPG) has brought unprecedented changes in the economic, trade and industrial scenario. LPG environment has exposed various organizations including the service sectors to the challenges of competition; service quality, cost and the competitive environment will help organizations to modernize. The impact of globalization and its implications for our country’s health care sector has rightly received wide attention and has been the subject of various health conclaves. With the state-of- the art medical procedures, equipment and facilities now available in India, patients from developed countries like Canada and Britain are choosing Indian Hospitals. Today India is not only well poised to meet the health care challenges of the millennium but also equipped with the talent and strength to contribute in further developing the health and economy of the world."Health is Wealth", the old saying still holds true. It is increasingly being recognized that good health is an important contributor to the productivity and economic growth at the same time it is first and foremost and an end itself. Perhaps, health care industry is one industry, which never faces a recession. Entry of private participants in the health insurance will enhance the accessibility of health care facilities to millions thus providing the right kind of health care services at affordable cost.